Relationship of psychological health impacts with nausea and vomiting among early pregnancy women in Hospital Universiti Sains Malaysia - Chai Shiaw, Yun
Nausea and vomiting in pregnancy (NVP) are troublesome symptoms that occur mainly in the first trimester of pregnancy. Its severity may influence the psychological health of pregnant women. Thus, a cross-sectional study conducted to examine the relationship of psychological health impacts with nausea and vomiting among early pregnancy women. Data collected using self-administered questionnaire. The psychological health investigated using General Health Questionnaire (GHQ) and mood and illness perception Visual Analogue Scale, and compared with the severity of nausea and vomiting as measured using Nausea and Vomiting in Pregnancy Instrument (NVPI). Sixty-four pregnant women were recruited as respondents. Statistical analysis carried out using SPSS program Version 12. The gestational age ranged from 10-16 weeks (13.17 ± 2.22). Fifty-eight {f= 90.6%) women reported nausea and vomiting during pregnancy, in which only 5 if= 7.8%) were having most severe nausea and vomiting. Psychological health among pregnancy women was good (11.30 ± 3.225). However, the perceived mental health (4.02 ± 3.61) and illness perception (8.74 ± 3.54) was significantly elevated. At the 95% of confidence interval, the Ho is rejected if p < 0.05. Pearson's correlation analysis of NVPI and psychological health showed that the severity of NVP X not correlated with total GHQ scores and GHQ subscales of anxiety and depression, social dysfunction, and loss of confidence (p > 0.05). Multiple linear regressions analysis showed that there was no association in NVP with mood perception (t = 1.989, p = 0.52) and GHQ (t = -0.224, p = 0.82). Nevertheless, illness perception (t = -2.575, p = 0.013) was associated with NVP after controlling age, race, educational level, occupation and gestational week. The researcher concluded that information on the strategies for NVP relieving and some support need provided to pregnant women, in order to help them to cope with NVP and thus improve their psychological health throughout the pregnancy.